Design Of Compact Tri-Polarized Antenna For Multiple Input Multiple Output (MIMO) System - Phoo, Kho Shin (2016)
In recent years, wireless communication system such as radar, navigation system, video conferencing, medical application and others has been widely developed. In order to meet the miniaturization requirements of portable communication equipment, an antenna with compact size has received much attention. Regardless of the application, most of the modern wireless communication systems require high data rate and channel capacity. With these provocations, Multiple Input Multiple Output (MIMO) system was introduced to provide efficient performance and combat multipath effect. The objective of this project was to design, simulate, and fabricate a compact tri-polarized antenna for MIMO system with operating frequency of 2.4GHz. In this project, antennas were designed by using inverted suspended method where the FR4 substrate and copper ground plane were separated with an air gap layer. Modified L-probe fed was used for all antenna designs where the strip line was printed on the upper side of the FR4 substrate and connected to the coaxial probe for ease of fabrication. The rectangular patch was printed at the lower side of the FR4 substrate. First of all, single polarizations for linear polarized (Design A) and circular polarized antennas (Design B) were designed. Then, dual-polarized antennas (Design C) were designed. Lastly, a compact tri-polarized antenna (Design D) was designed with a combination of three different polarizations; including linear polarization(LP), left-handed circular polarization (LHCP) and right-handed circular polarization(RHCP). All the antenna designs were simulated by using Computer Simulation Technology (CST) software. Single-polarized antenna, dual-polarized antenna and tripolarized antenna were successfully designed and achieved design specifications. Based on the simulation and measurement results, the designed antennas covered frequency of 2.4GHz with reflection coefficient below -10dB. The simulated bandwidths of the designed antenna were more than 200MHz for the broadband specification. The simulated axial ratio result was used to determine the performance of polarizations, in which the axial ratio for linear polarized was above 3dB and the axial ratio for circular polarized was below 3dB. Overall, the reflection coefficient, total efficiency, directivity, gain, axial ratio, and bandwidth of compact tri-polarized antenna showed good responses. The measurement results were almost similar to the simulation results. Therefore, this compact broadband tripolarized antenna that is capable of performing in three different polarizations is suitable to be applied in MIMO system that requires polarization diversity.